МОЙ МУДРЫЙ ОТЕЦ - Лазаревна Сарьян Cофья (Musical Armenia, 2010)
Martiros Saryan’s House Museum’s Director of Archives, L. Saryan’s daughter’s Sofia Lazar Saryan “My wise father” article is an memoirs. It presents about the conditions created by the peaceful family, where the composer worked, the rest in AC of RA “Dilijan” creative home, some of the details of the works (Symphony, “Andante & Presto” for violin and chamber orchestra ), also describes the atmosphere of hospitable house of Saryans: Characterized by a special warmth, the wisdom, and character, who is always with her, as an example.